The Impact of State Intervention on Social Capital of Fishermen Community in Small Islands - Anwar, Sakaria J; Kolopaking, Lala M; Kinseng, Rilus A; Hubeis, Aida Vitayala S. (Komunitas, 2014)
This paper aims to discuss the impact of state intervention on social capital of fishermen community in small islands. The research was conducted in Barrang Lompo Island, Makassar. The data was collected through in-depth interview and limited observation from twelve informants determined by snowball sampling. Questionnaires were also spread to about 40 respondents. The data was then analyzed qualitatively to explain research’s data and facts. The results of the research show that state intervention for the last ten years on small islands communities has impact on various aspects such as the diminishing loyalty and trust among locals to the government. Therefore, the intervention reduce the community’s participation, individually and collectively, in development activities. The situation, in turn, could affect the diminishing political capacity of the locals and government in the implementation of development in the islands. The state intervention, however, strengthened social solidarity, local value practices and the enthusiasm to understand religious values which in turn could tighten the internal bond of a community. This bond can become a potential strength to build communities in small islands. Tulisan ini bertujuan untuk mendiskusikan dampak intervensi negara pada kapital sosial komunitas nelayan di pulau-pulau kecil. Penelitian ini dilakukan di Pulau Barrang Lompo, Makassar. Pengumpulan data dilakukan melalui wawancara mendalam dan observasi terbatas dari dua belas informan ditentukan oleh snowball sampling. Kuesioner juga menyebar ke 40 responden. Data tersebut kemudian dianalisis secara kualitatif untuk menjelaskan data penelitian dan fakta. Hasil penelitian menunjukkan bahwa intervensi negara selama sepuluh tahun terakhir pada masyarakat pulau-pulau kecil memiliki dampak pada berbagai aspek seperti, mengurangi loyalitas dan kepercayaan di antara penduduk setempat kepada pemerintah. Oleh karena itu, partisipasi mereka, secara individu dan kolektif, dalam kegiatan pembangunan kurang. Ini akan berakibat pada berkurangnya kapasitas politik penduduk setempat dan kapasitas pemerintah dalam pelaksanaan pembangunan pulau. Kendati demikian intervensi negara juga memperkuat solidaritas sosial, praktek nilai lokal dan semangat untuk memahami nilai-nilai agama yang pada gilirannya dapat memperkuat ikatan internal masyarakat. Ikatan ini selanjutnya dapat menjadi kekuatan potensial untuk membangun masyarakat di pulau-pulau kecil.